Urbanicity, Persecutory Delusions, and Clinical Intervention: The Development of a Brief CBT Module for Helping Patients with Persecutory Delusions Enter Social Urban Environments. Issue 1 (9th August 2013) - Freeman, Daniel; Waller, Helen; Harpur-Lewis, Ruth Ann; Moore, Rosanna; Garety, Philippa; Bebbington, Paul; Kuipers, Elizabeth; Emsley, Richard; Dunn, Graham; Fowler, David; Jolley, Suzanne
Abstract : Background: Substantial epidemiological research has shown that psychotic experiences are more common in densely populated areas. Many patients with persecutory delusions find it difficult to enter busy social urban settings. The stress and anxiety caused by being outside lead many patients to remain in-doors. We therefore developed a brief CBT intervention, based upon a formulation of the way urban environments cause stress and anxiety, to help patients with paranoid thoughts to feel less distressed when outside in busy streets.Aims: The aim was to pilot the new intervention for feasibility and acceptability and gather preliminary outcome data.Method: Fifteen patients with persecutory delusions in the context of a schizophrenia diagnosis took part. All patients first went outside to test their reactions, received the intervention, and then went outside again.Results: The intervention was considered useful by the patients. There was evidence that going outside after the intervention led to less paranoid responses than the initial exposure, but this was only statistically significant for levels of distress.Conclusions: Initial evidence was obtained that a brief CBT module specifically focused on helping patients with paranoia go outside is feasible, acceptable, and may have clinical benefits. However, it could not be determined from this small feasibility study that any observed improvements were due to the CBT intervention. Challenges in this area and future work required are outlined.